Resolvin D2 prevents secondary thrombosis and necrosis in a mouse burn wound model - Bohr, Stefan; Patel, Suraj J; Sarin, Dhruv; Irimia, Daniel; Yarmush, Martin L.; Berthiaume, Francois (Wound repair and regeneration, 2013)
Deep partial thickness burns are subject to delayed necrosis of initially viable tissues surrounding the primary zone of thermally induced coagulation, which results in an expansion of the burn wound, both in area and depth, within 48 hours postburn. Neutrophil sequestration and activation leading to microvascular damage is thought to mediate this secondary tissue damage. Resolvins, a class of endogenous mediators derived from omega‐3 polyunsaturated fatty acids, have been shown to regulate the resolution of inflammation. We hypothesized that exogenous resolvins could mitigate the deleterious impact of the inflammatory response in burn wounds. Using two different mouse burn injury models involving significant partial thickness injuries, we found that a systemically administered single dose of resolvin D2 (RvD2) as low as 25 pg/g bw given within an interval of up to 4 hours postburn effectively prevented thrombosis of the deep dermal vascular network and subsequent dermal necrosis. By preserving the microvascular network, RvD2 enhanced neutrophil access to the dermis, but prevented neutrophil‐mediated damage through other anti‐inflammatory actions, including inhibition of tumor necrosis factor‐α, interleukin‐1β, and neutrophil platelet–endothelial cell adhesion molecule‐1. In a clinical context, RvD2 may be therapeutically useful by reducing the need for surgical debridement and the area requiring skin grafting.